English for Tour Guide: Kegiatan Pengabdian kepada Masyarakat bagi Guru SMK di Purbalingga: English for Tour Guide: A Community Service for Vocational School Teachers in Purbalingga - Ningsih, Sri Kusuma; Warni, Silih (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2024)
This community service program seeks to help teachers enhance their English communication abilities, and in particular English for Tour Guide. Aside from that, it provides information, insight and creative inspiration in teaching and learning activities, which can indirectly contribute to the growth of local tourism. This activity was carried out utilizing a training method based on the results of an analysis of needs and challenges encountered at SMK Negeri 1 Bojongsari in terms of English mastery, conducted through interviews and observations. The training method used is through presentation of material, drilling, and evaluation. This PKM activity is for vocational school teachers and students, as well as UHAMKA lecturers and students. This training event went off without a hitch, as planned by the UHAMKA PKM team. Participants were enthusiastic and involved in creating a conducive atmosphere till the program ended. The evaluation results indicate that more time is needed for practice and evaluation. Furthermore, it is advised that existing activities such as comparable training, be held on a regular basis to develop teachers' teaching skills.